Birdman : la inesperada virtud de la ignorancia - Iñárritu, Alejandro G., 1963-; Keaton, Michael; Speak Up (DVD (Speak Up), 2014)
Illustrated upon the progress of his latest Broadway play, a former popular actor's struggle to cope with his current life as a wasted actor is shown.